Bone mineral density in triathletes over a competitive season - McClanahan, B. S.; Ward, K. D.; Vukadinovich, C.; Klesges, R. C.; Chitwood, L.; Kinzey, S. J.; Brown, S.; Frate, D. (Journal of Sports Sciences, 2002)
There is evidence from previous cross-sectional studies that high volumes of certain sports, including running, swimming and cycling, may have a negative impact on bone mineral density. The aim of the present study was to evaluate prospectively the effects of high athletic training in individuals who engage in high volumes of all three of these activities (triathletes). Bone mineral density for the total body, arms and legs was determined by dual-energy X-ray absorptiometry in 21 competitive triathletes (9 men, 12 women) at the beginning of the training season and 24 weeks later. Age, body mass index, calcium intake and training volume were also recorded to examine potential mediators of bone mineral density change. Men had greater bone mineral density at all sites than women. No significant changes were observed over the 24 weeks for either total body or leg bone mineral density. Bone mineral density in both arms increased by approximately 2% in men (P < 0.03), but no change was observed for women. Change in bone mineral density at all sites was unrelated to age, body mass index, calcium intake and training volume. The results suggest that adverse changes in bone mineral density do not occur over the course of 6 months of training in competitive triathletes.